1998
DOI: 10.1051/aas:1998299
|View full text |Cite
|
Sign up to set email alerts
|

Identification of selected sources from the ROSAT Galactic Plane Survey. I.

Abstract: Abstract. We report on optical searches in the error circles of 93 ROSAT survey sources located at low galactic latitudes (|b| < 20• ). These sources were extracted from the ROSAT Galactic Plane Survey using various selection criteria on hardness ratio, X-ray and optical brightness and integrated galactic absorption in the direction of the source. We find optical identifications in 76 cases, among which are 25 new AGN, 6 new CVs and a new Be/X-ray binary. In order to illustrate the relevance of the source sele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 21 publications
(37 reference statements)
7
121
1
Order By: Relevance
“…In order to characterise the nature of the secondary in RX J1914.4+2456, Ramsay et al (2000) Ramsay et al (2002b) where the magnitudes are with respect to Star 'B' of Motch et al (1996).…”
Section: Optical/ir Coloursmentioning
confidence: 99%
“…In order to characterise the nature of the secondary in RX J1914.4+2456, Ramsay et al (2000) Ramsay et al (2002b) where the magnitudes are with respect to Star 'B' of Motch et al (1996).…”
Section: Optical/ir Coloursmentioning
confidence: 99%
“…The low fraction of AGN in the two high-galactic latitude identification programs might be due to the bias against fainter counterparts for which objective prism spectra were either not available or inconclusive -this would rise the fraction of bright-vs.-faint counterparts, and thus the ratio of stellar-vs.-extragalactic objects. The nearly complete lack of AGN in our low-galactic latitude field as compared to the nearly 20% fraction in Motch et al (1998) is most likely due to their survey covering galactic latitudes up to ±20 • , and our optical material not being deep enough to recover absorbed AGN behind the Milky Way disk. Figure 39 shows the histogram of the distances of the secure optical counterparts to their respective centroid ROSAT X-ray position for the Coma field.…”
Section: Identification Results and Global Statisticsmentioning
confidence: 73%
“…These authors find relative source class fractions of 42.1% AGN, 40.7% stars, 11.6% cluster of galaxies, and 3.9% galaxies. The ROSAT galactic plane survey (Motch et al 1998) achieved identification of 76 out of 93 sources, among them 40 bright/active stars, 25 AGN and 6 cataclysmic variables (this survey selected according to X-ray brightness and various hardness ratio criteria, so did not aim at completeness in a given area). These relative fractions of source types are largely consistent with our results (Table 12), though some differences show up.…”
Section: Identification Results and Global Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motch et al 1998;Véron-Cetty & Véron 2001;Kollatschny et al 2008). Mainly based on the detection of the high-ionisation line [Ne v] in the Spitzer/IRS spectra, the Seyfert 1.9 nucleus has been associated with the western galaxy of the system, coincident with 1SXPS J050819.8+172149 (Petric et al 2011;Alonso-Herrero et al 2012;Stierwalt et al 2013Stierwalt et al , 2014, see also the optical classification reported by Alonso-Herrero et al 2013).…”
Section: Sxps J0508198+172149mentioning
confidence: 93%